2020
DOI: 10.1111/jnc.15186
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between α7 nicotinic acetylcholine receptors, pannexin‐1 channels and P2X7 receptors elicit exocytosis in chromaffin cells

Abstract: Pannexin‐1 (Panx1) forms plasma membrane channels that allow the exchange of small molecules between the intracellular and extracellular compartments, and are involved in diverse physiological and pathological responses in the nervous system. However, the signaling mechanisms that induce their opening still remain elusive. Here, we propose a new mechanism for Panx1 channel activation through a functional crosstalk with the highly Ca2+ permeable α7 nicotinic acetylcholine receptor (nAChR). Consistent with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 127 publications
1
21
0
Order By: Relevance
“…In order to detect submembrane localized Ca 2+ signals, HeLa cells grown on coverslips were transfected with a genetically encoded Ca 2+ indicator protein pN-Lck-GCAMP3 plasmid (a generous gift from Baljit Khakh, Los Angeles, CA, Addgene plasmid no. 26974) as previously described (47). Cells were imaged 24 to 48 h posttransfection by TIRF microscopy using an inverted microscope (Eclipse Ti-E; Nikon) implemented with a 100× APO TIRF objective (numerical aperture 1.49; Nikon) and a Perfect Focus Unit TI-ND6-PFS (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect submembrane localized Ca 2+ signals, HeLa cells grown on coverslips were transfected with a genetically encoded Ca 2+ indicator protein pN-Lck-GCAMP3 plasmid (a generous gift from Baljit Khakh, Los Angeles, CA, Addgene plasmid no. 26974) as previously described (47). Cells were imaged 24 to 48 h posttransfection by TIRF microscopy using an inverted microscope (Eclipse Ti-E; Nikon) implemented with a 100× APO TIRF objective (numerical aperture 1.49; Nikon) and a Perfect Focus Unit TI-ND6-PFS (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…With the same cell model, the central role of extracellular and intracellular sphingosine-1-phosphate, a complex signaling lipid, is demonstrated for the first time by using CFA and especially by analyzing the PSF properties (that reflects the fusion pore stability; see Figure 2) [9]. CFA also contributes to important findings related to the interconnected role between pannexin-1 channels and some purinergic and nicotinic acetylcholine receptors to trigger exocytosis [10]. In the same way, the effects of some signaling pathways from a receptor tyrosine kinaselike EPHB6 on catecholamines secretion are undoubtedly proven with CFA at chromaffin cells with important consequences on the relationship between effect on catecholamine secretion and blood pressure regulation [11].…”
Section: Contributions Of the Historical Cfa Technique Cfa As A Usual Technique To Investigate Exocytosismentioning
confidence: 84%
“…Panx1 channels localize in the cell membrane and play a relevant role in the release of ATP from different cell types [ 170 ]. Different stimuli capable of activating Panx1 channels have been reported, including voltage [ 173 ], membrane stretching [ 174 , 175 ], intracellular Ca 2+ augmentation [ 175 , 176 ], and its C-terminal domain proteolysis [ 177 ]. However, it was recently shown that Panx1 is not directly sensitive to stretching instead, stretch stimulates other channels that allow the entry of Ca 2+ promoting the activation of the Ca 2+ /calmodulin-dependent protein kinase II (CaMK ll), which phosphorylates Panx1, causing a conformational change of the channel that allows the passage of ATP through its “lateral tunnels” [ 175 ].…”
Section: Connexin and Pannexin Channels In Muscular Dystrophiesmentioning
confidence: 99%